Bacterial mortality caused by viral lysis in Nha Trang bay, South central Vietnam - Hai, Doan Nhu; Thanh, Nguyen Van; Thoi, Nguyen Chi; Lam, Nguyen Ngoc (Academia Journal of Biology, 2015)
Bacteria play an important role in microbial loop in marine waters and are strongly regulated by top-down controls by two groups, virus and microprotozoa. Bacterial mortality rates, because of viral lysis and microprotozoan grazing, were estimated using dilution method in Nha Trang bay in December 2014. The bacterial mortality rates were marked different among sampling sites and reflected by different in environmental conditions and layers in water column. In Nha Trang bay, the viral lysis on bacteria was, in similar trend with previous studies, high where their main hosts abundance, such as at surface and in the estruarine front area. Bacterial growth rate was low in Cai estuary and higher in mid of Nha Trang Bay and Hon Tam stations. The bacterial mortality rates in Nha Trang Bay were mainly because of the viral lysis (1.59-2.05 day-1) rather than of microprotozoan grazing (0.00-0.36 day-1). The microprotozoan grazing on bacteria in Cai estuary was significantly higher than in others sites (0.36 day-1 versus 0.00-0.05 day-1).